1986
DOI: 10.1063/1.337177
|View full text |Cite
|
Sign up to set email alerts
|

Electronical properties of metal-insulator-semiconductor devices prepared on thermally treated InP in phosphorus overpressure

Abstract: The effect of excess phosphorus vapor during the process of MIS structures on InP is analyzed in detail. It is shown that the density of interface state distribution is considerably modified after in situ thermal precleaning of the substrate in phosphorus overpressure (suppression of the Fermi-level pinning and significant reduction of the density of surface states near midgap). Phosphorus overpressure also provides an efficient protection of the surface during the insulator deposition. Fermi-level pinning in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
6

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
4
0
6
Order By: Relevance
“…These states may be identified as the antisite dangling bonds cation-on-anion site (Inp) according t o the previous theoretical defect model developed by Allen et al . [32) and their coworkers, More recently, it has been shown that after a brief exposing of I n P substrate t o ambient atmosphere and after precleaning in P over-pressure [33], the C-U plots of A1,0,-InP MIS structures show the same plateau in the frequency range 1 to 100 kHz.…”
Section: Capacitance and Conductance Measurements At Different Frequementioning
confidence: 87%
“…These states may be identified as the antisite dangling bonds cation-on-anion site (Inp) according t o the previous theoretical defect model developed by Allen et al . [32) and their coworkers, More recently, it has been shown that after a brief exposing of I n P substrate t o ambient atmosphere and after precleaning in P over-pressure [33], the C-U plots of A1,0,-InP MIS structures show the same plateau in the frequency range 1 to 100 kHz.…”
Section: Capacitance and Conductance Measurements At Different Frequementioning
confidence: 87%
“…PÉRATURES. -La figure 3 représente, à la fréquence 1 kHz, les courbes C-V pour des températureis variant de 150 K à 373 K. D'une manière générale, pour une tension donnée, la capacité de la structure augmente avec la température comme pour les courbes C-V en fonction de la fréquence (Fig. 2) ; on n'observe pas de saturation à forte polarisation ce qui peut s'expliquer par la forte densité d'états d'interface au voisinage de la bande de conduction (1013 cm-2 eV-1) et par la faible résistivité de l'oxyde qui se manifeste par des courants de fuite [14,15].…”
Section: Caractéristiques C-v a Différentes Tem-unclassified
“…La capacité et la conductance des structures sont mesurées à l'aide d'un banc de mesures automatiques construit au laboratoire [5,6]. 3. Résultats et interprétation.…”
unclassified
“…Les états de surface d'origines diverses ont été envisagés, liés soit à un oxyde natif mal contrôlé, à des lacunes de phosphore induites (1) Cet article avait été proposé pour le numéro spécial Semi-conducteurs III-V. Sa parution a été retardée pour des raisons matérielles indépendantes de l'éditeur. par des traitements de surface trop énergétiques ou favorisées par les températures élevées lors des processus d'élaboration [1,2].…”
unclassified
“…La partie supérieure de la bande interdite, explorée jusqu'à une distance Ee -E légèrement inférieure à 0,1 eV semble exempte de défauts, aucun autre signal DLTS n'étant enregistré pour une température descendant à 77 K. Certains auteurs ont déjà constaté que l'oxyde natif permettait de réduire la densité d'états au voisinage de la bande de conduction [2]. C'est un résultat intéressant que de constater qu'après un traitement complexe et comportant en particulier une phase en plasma, mais à basse énergie, un seul état domine à l'interface.…”
unclassified